Desenvolvimento de produto extrudado tipo snack com adição de farinha de berinjela: estudo tecnológico e sensorial - Magalhães, Ana Lídia Martins (2019)
The extruded snacks present themselves as versatile products that stand out for their practicality, however do not offer a nutritional appeal. The purpose of this study was to develop and evaluate formulations of extruded snacks from a mixture of cornmeal and eggplant flour, analyzing the physical and technological characteristics and the centesimal composition of the product. The evaluated formulations had the incorporation of up to 20% of eggplant flour and initial moisture of the raw material of 14 to 18%. The snack was produced in a twin screw extruder, on an industrial scale. The extrusion parameters were kept fixed, employing three extrusion zones with temperatures of 100, 180 and 180 °c; Screw speed of 153 rpm; Feed rate of 170 kg/h; and circular matrix of 3.5 mm in diameter. To check which parameters influence the properties of snacks expanded, there was a central composite rotational design (DCCR) whose independent variables content of eggplant and initial moisture mixing. The dependent variables evaluated were: the radial expansion index (IER), the apparent density (DA), water solubility index (ISA) and water absorption index (IAA). The results were analyzed by response surface methodology. Evaluating the physical and technological characteristics, the snacks presented high radial expansion index and low apparent density, important aspects for this type of product. Through the results of the dependent variables and the evaluation of the sensorial acceptance four formulations were selected and characterized as physical-chemical composition and evaluated with sensorial intensity test associated with check-all-that-apply (CATA). The treatments chosen and evaluated presented a high content of dietary fiber and lipids, being classified as food with high fiber content, according to the Brazilian current legislation. In the sensory analysis the formulations chosen received average grade from 5.8 to 6.6 for the overall impression attribute, in the hedonic scale of 9 points, being located in the category “indifferent” to “moderately liked” and reaching a positive purchase intention of 58%, being the most accepted snack the processed with 11.5% of eggplant flour and 17% of initial moisture of the raw materials. Based on these results, the snack developed with the incorporation of eggplant flour presents potential for commercialization because it presents satisfactory acceptance and buy intention, in addition to having high fiber content.